An epigenetic activation role of Piwi and a Piwi-associated piRNA in Drosophila melanogaster. - Yin, H.; Lin, H. (Nature, 2007)
Heterochromatin, representing the silenced state of transcription, consists largely of transposon-enriched and highly repetitive sequences. Implicated in heterochromatin formation and transcriptional silencing in Drosophila are Piwi (P-element induced wimpy testis) and repeat-associated small interfering RNAs (rasiRNAs). Despite this, the role of Piwi in rasiRNA expression and heterochromatic silencing remains unknown. Here we report the identification and characterization of 12,903 Piwi-interacting RNAs (piRNAs) in Drosophila, showing that rasiRNAs represent a subset of piRNAs. We also show that Piwi promotes euchromatic histone modifications and piRNA transcription in subtelomeric heterochromatin (also known as telomere-associated sequence, or TAS), on the right arm of chromosome 3 (3R-TAS). Piwi binds to 3R-TAS and a piRNA uniquely mapped to 3R-TAS (3R-TAS1 piRNA). In piwi mutants, 3R-TAS loses euchromatic histone modifications yet accumulates heterochromatic histone modifications and Heterochromatin Protein 1a (HP1a). Furthermore, the expression of both the 3R-TAS1 piRNA and a white reporter gene in 3R-TAS becomes suppressed. A P element inserted 128 base pairs downstream of the 3R-TAS1 piRNA coding sequence restores the euchromatic histone modifications of 3R-TAS and the expression of 3R-TAS1 piRNA in piwi mutants, as well as partly rescuing their defects in germline stem-cell maintenance. These observations suggest that Piwi promotes the euchromatic character of 3R-TAS heterochromatin and its transcriptional activity, opposite to the known roles of Piwi and the RNA-mediated interference pathway in epigenetic silencing. This activating function is probably achieved through interaction with at least 3R-TAS1 piRNA and is essential for germline stem-cell maintenance.